THE IMPACT OF HUMAN RESOURCE MANAGEMENT PRACTICES ON INCREASING EMPLOYEE PRODUCTIVITY APPLIED ON BAHRAIN WORKPLACE - ALDOSERI, AHMED FAISAL JABOR (Digital Repository of Theses - SSBM Geneva, 2022)
The idea of this study was to address a recommendation to increase employee productivity in the Bahraini workplace, by examining the impact of Human Resource Management (HRM) on such increase of productivity in Bahrain’s workplace. An exploration and comparison of HRM practices was carried out using desk research for articles and books on HRM and Productivity as well as interviews with various ranks within the Bahraini work settings. It was found that HRM does have a great impact on productivity and within the Bahraini workplace an understanding of core concepts from the HRM and other theories can be shown to provide successful changes and innovations that will lead to higher productivity. Where employees are treated as human capital and not as a commodity product, highly significant and successful improvements can be achieved.